2018
DOI: 10.3390/ijerph15081608
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic Analysis of Unsafe Behavior by Coal Miners: Multi-Dimensional Description of the Pan-Scene Data

Abstract: As a high-risk occupation, coal mining has many accidents, primarily due to the unsafe behavior of coal miners. Based on the research of analysis of unsafe behavior and pan-scenario data of miners, a theoretical framework for the analysis of unsafe behavior characteristics was proposed in this paper. The collected data were divided into realistic scenes and abstract scenes according to different manifestations; the pan-scene data were described from the eight dimensions of time, behavioral trace, location, beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 53 publications
(55 reference statements)
0
23
0
Order By: Relevance
“…[5]. Complex working conditions, the harsh working environment, and many dangerous factors have formed a severe production situation in coal mines [6,7]. This situation has not only caused adverse social impacts, but also widespread concern in the international community, directly affecting the image of the Chinese government and foreign trade of enterprises.…”
Section: Introductionmentioning
confidence: 99%
“…[5]. Complex working conditions, the harsh working environment, and many dangerous factors have formed a severe production situation in coal mines [6,7]. This situation has not only caused adverse social impacts, but also widespread concern in the international community, directly affecting the image of the Chinese government and foreign trade of enterprises.…”
Section: Introductionmentioning
confidence: 99%
“…The hidden danger of job sites and violation images can be used as realistic data, recording the occurrence time of the accident, the behavior process of the individual, and the situation of all things, which can clearly and truly reflect the unsafe behavior and the safety risk points of miners [21]. The accident report records the process, the cause, the corrective action, and the result of the accident.…”
Section: The Targeted Intervention Nodes Of Miners’ Unsafe Behaviormentioning
confidence: 99%
“…However, although China has made significant progress in coal mining technology and safety equipment configuration [1], coal mine accidents still occur frequently [2,3], and coal mine safety production is facing difficulties. Previous studies found that human factors have become the leading cause of coal mine accidents [4][5][6]. Accidents caused by unsafe human behavior accounted for 96.5% of the total number of accidents [7], and findings regarding workplace behavior and the health and safety of coal workers are not promising [8].…”
Section: Introductionmentioning
confidence: 99%